HIPERTERMIA EM RATOS INDUZIDA PELA LESAO ELETROLITICA DO MESENCEFALO: PARTICIPACAO DAS PROSTAGLANDINAS - Lobato de Menezes, C. E. [UNESP] (My University, 1993)
The present studies were conducted to determine the role of prostaglandins in the etiology of a rise of body temperature observed in rats after electrolytic lesion made on the dorsal mesencephalic areas. This hyperthermia was abolished by intraperitoneal administration of indomethacin, an inhibitor of prostaglandins synthesis. These results strengthen the suggestion of a similar mechanism for both neurogenic hyperthermia and the fevers produced by pyrogens. However, until further experiments are carried out, the possibility of lesion in producing hyperthermia by different mechanisms cannot be ruled out.
Hyperthermia in rats induced by mesencephalic electrolytic lesion: Participation of prostaglandins
Keywords: indomethacin; induced hyperthermia; mesencephalon; prostaglandins; rats; wounds and injuries; indometacin; prostaglandin derivative; prostaglandin synthesis inhibitor; unclassified drug; animal experiment; animal model; brain injury; controlled study; hyperthermia; intravenous drug administration; male; nonhuman; rat; thermoregulation